2015
DOI: 10.1515/ijamh-2015-5010
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and adolescent suicide: a proposal for physician education

Abstract: Suicide is the second leading cause of death among adolescents aged 14-19 years. Pediatricians report strong interest in receiving additional training to reduce suicide mortality, and physician education is one of the most robust means of suicide prevention. However, many studies suggest that existing educational methods and means leave much room for improvement. In light of the emerging evidence that emotion regulation (ER) deficits are significantly associated with adolescent suicide, this paper proposes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Emotion regulation may involve relatively automatic as well as more conscious behavioral attempts to modulate emotional states, including by altering one's external environment or the manner of an emotional expression (Eisenberg and Spinrad, 2004). Numerous studies have examined the links between emotion regulation and well-being across the lifespan (Joseph and Newman, 2010;Röll et al, 2012;Rice, 2015;Daniel et al, 2020;Zamani Zarchi et al, 2020), with emotion regulation typically being viewed as "prohedonic, " meaning that it is always directed at optimizing one's well-being (Riediger and Klipker, 2014). However, some studies have suggested that this may not always be true-that emotion regulation can sometimes be "contrahedonic"-since people may dwell on negative experiences in order to intensify them, or to lessen positive emotional experiences (Erber and Erber, 2000;Riediger et al, 2009).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Emotion regulation may involve relatively automatic as well as more conscious behavioral attempts to modulate emotional states, including by altering one's external environment or the manner of an emotional expression (Eisenberg and Spinrad, 2004). Numerous studies have examined the links between emotion regulation and well-being across the lifespan (Joseph and Newman, 2010;Röll et al, 2012;Rice, 2015;Daniel et al, 2020;Zamani Zarchi et al, 2020), with emotion regulation typically being viewed as "prohedonic, " meaning that it is always directed at optimizing one's well-being (Riediger and Klipker, 2014). However, some studies have suggested that this may not always be true-that emotion regulation can sometimes be "contrahedonic"-since people may dwell on negative experiences in order to intensify them, or to lessen positive emotional experiences (Erber and Erber, 2000;Riediger et al, 2009).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Overwhelmingly, male adolescents commit suicide more often than females: only in China, Cuba, Ecuador, El Salvador, and Sri Lanka do young women commit suicide more than men (26). Within this special issue, the importance of impulsivity and emotion dysregulation in adolescent suicide has been presented (27). However, it is important to note for this piece concerning male adolescents that suicidal males are more likely to exhibit an impulsive presentation than suicidal females (28,29).…”
Section: Epidemiology and The Importance Of Impulsivitymentioning
confidence: 99%
“…Acting with a perspective toward developing constructive solutions by analyzing negative situations is within the scope of positive thinking (Gür & Eser, 2022). What needs to be emphasized here is highlighting the positive aspects of life and determining strategies for a more quality life (Rice, 2015). In other words, although evaluations are made on negative events, analyzing experienced emotions and situations instead of feeling helpless and taking constructive measures for life by making evaluations from different frameworks is also included in the scope of positive thinking (Peterson, 2009;Seligman, 2012).…”
Section: Introductionmentioning
confidence: 99%